Holistic Approach for Teaching Tuberculosis in Medical Education - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Tabriz University of Medical Sciences, 2014)
Tuberculosis (TB) is the foremost cause of mortality attributed to a curable infectious disease globally, accounting for 8.6 million new cases in the year 2012, of which India alone has a share of almost 25% of cases. Medical colleges have been acknowledged as tertiary level health care centers and have a key role in the diagnosis and management of different types of TB cases. However, a wide range of barriers and deficiencies have been acknowledged in the medical education curriculum over a period of time with regard to teaching of TB control. To combat the magnitude of TB on the health sector in Indian set-up, there is a crucial need for establishing a mutual and complementary partnership between policy makers, delegates from the medical colleges, and the regulatory body for medical education. In summary, medical students are the future health care providers for the general population and thus a well-organized medical education curriculum can play a significant role in reducing the magnitude of tuberculosis in the coming decade.